Analysis of SDN-Orchestrated Solutions for Heterogeneous IoT in 6G Networks - Lanka, Surekha; Tripura, Shuvra (IRO Journal on Sustainable Wireless Systems, 2026)
The sixth generation (6G) networks facilitate the provision of large-scale, heterogeneous Internet of Things (IoT) applications with a variety of requirements such as latency, reliability, scalability and data rates that are higher than the limits of traditional network architectures. The drawbacks of current network architectures for implementing heterogeneous IoT applications increased in dynamicity and complexity connected to these kinds of networks. SDN Solutions provide an effective approach to implement the heterogeneous IoT for 6G Networks. The purpose of this review is to provide a comprehensive overview of SDN-based architecture, orchestration mechanism and control strategies includes to connect and improve the performance of related technologies such as NFV, edge and fog computing, network slicing and AI. This paper will explain the SDN-based orchestration improves interoperability, resource allocation, quality of service and security for heterogeneous IoT use cases. This study concludes with future research directions for smart, autonomous and resilient SDN-enabled IoT systems in next-generation 6G Networks.